1995
DOI: 10.1111/j.1365-2265.1995.tb00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac flow velocity in women with the polycystic ovary syndrome

Abstract: An inverse relation between serum fasting insulin level and left ventricular systolic outflow parameters suggests that insulin is associated with the decreased systolic flow velocity observed in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Also, subclinical impairment of LV systolic and diastolic function as indicated by lower peak strain, peak systolic strain rate, peak early diastolic strain rate, and peak early diastolic velocity was demonstrated in with PCOS and IR group (34). In addition, Prelevic et al (30) reported that systolic flow velocity is lower in PCOS than in age-matched control women, and there is an inverse relationship between serum fasting insulin and LV systolic outflow parameters; fur- thermore, increased insulin levels in PCOS are associated with decreased cardiac flow. In the present study, we found waistto-hip ratio, insulin, HOMA-IR, LDL levels were higher in PCOS group and GLS correlation with the hip-to-waist ratio, LDL values.…”
Section: Discussionmentioning
confidence: 91%
“…Also, subclinical impairment of LV systolic and diastolic function as indicated by lower peak strain, peak systolic strain rate, peak early diastolic strain rate, and peak early diastolic velocity was demonstrated in with PCOS and IR group (34). In addition, Prelevic et al (30) reported that systolic flow velocity is lower in PCOS than in age-matched control women, and there is an inverse relationship between serum fasting insulin and LV systolic outflow parameters; fur- thermore, increased insulin levels in PCOS are associated with decreased cardiac flow. In the present study, we found waistto-hip ratio, insulin, HOMA-IR, LDL levels were higher in PCOS group and GLS correlation with the hip-to-waist ratio, LDL values.…”
Section: Discussionmentioning
confidence: 91%
“…In a study of 26 PCOS patients, a significant negative correlation was observed between the serum fasting insulin concentration and left ventricular systolic outflow parameters. 3) Regardless of the results of the above studies, surprising results have been published on the rates of morbidity and mortality from coronary heart disease in this syndrome. 22,23) In a retrospective study, the hospital records of 786 women with PCOS in the United Kingdom were analysed.…”
Section: Discussionmentioning
confidence: 98%
“…14 The results of those few studies in vessels outside the pelvis suggest decreased flow over the aortic arch 15 and increased resting forearm flow, and in a previous study we reported lower pulsatility index (vascular resistance) and back pressure, suggestive of reduced vascular tone in the ICA in women with PCOS, 16 whereas asymptomatic women with PCO exhibited similar changes of lesser magnitude. In a recent study, we investigated vascular responses in women with PCOS and observed a paradoxical constrictor response to hypercapnia in the ICA.…”
mentioning
confidence: 82%